Strategi Dinas Perindustrian dan Perdagangan Kota Medan dalam Perkembangan Produk Ekspor - Dhea Savitri; Nurhayati Nurhayati (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This research analyzes the strategy of the Medan City Industry and Trade Office in developing export products. From BPS data (Central Statistics Agency) in December 2021, exports in North Sumatra increased by 14.96 percent. Send out is one of the parts of Gross Domestic Product (GDP) that can support the recuperation of the public economy. Concerning the system that should be possible in creating trade items, one of which is keeping up with send out business sectors and primary items. By keeping up with the financial market and the fundamental results of the economy will increment and the principle send out items will be better known in global exchange.